Stochastic Modelling of the Dynamics of the SARS-CoV-2 Epidemic: An Africa Perspective - Rasaki, Olawale Olanrewaju; Nafiu, Lukman Abiodun; Abdisalam, Hassan Muse; Thierno, Souleymane Barry (American Journal of Mathematics and Statistics, 2021)
Africa being one of the seven (7) continents is not exempted in the epidemic catastrophe of the respiratory virus called SARS-CoV-2 battling the world. Africa in its totality has been enforcing containment measures to prevent, curb, reduce and contain the widespread of the virus via social-distancing, curfews, economic lockdown in phases. In this paper, we modelled the course of action of the SARS-CoV-2 virus in Africa and its five regions at approximately a year (as at 23/02/2021) of the pandemic via a five transitional compartments SIERD (Susceptible → Exposed→ Infected →Recovery → Dead) model. The datasets for the number of confirmed cases of the virus as well as the number of recoveries and deaths due to the virus as at 23/02/2021 were extracted from Africa Centre for Disease Control (Africa CDC). It was carved-out from the SIERD model, that the rate of contracting the virus in Africa during each individual contact is 36.61%, while the rate in the Central, Eastern, Northern, Southern and Western parts were estimated to be 21.73%, 62.43%, 72.45% and 16.43 respectively. However, the recovery rate from the SARS-CoV-2 infection was 66.35% with Central, Western and Eastern regions dominating with 99.12%, 99.26% and 84.32% rates respectively. Lastly, the overall Infection Fatality rate in Africa was estimated to be 26.16%, while it carted across the Central, Eastern, Northern, Southern and Western regions with 15.3%, 20.4%, 31.6%, 39.4%, and 24.1% respectively.